The Role of Faith Bases Organizations in Enhancement of the Social Welfare Among the Rural Poor Households in Nyamweru sub-county, Kabale district; A case Study of Caritas Kabale diocese. - Hategekimana, Donisian (Kabale University, 2018)
FBOs have for a long time committedly made positive contributions towards provision of education, support in agriculture, skills, health to enhance social welfare but some people in rural areas still have low income, have poor health standards, have no food security, and have limited skills and lack employment due to low levels of education hence poor social welfare. This study was conducted to assess the contribution of FBOs (Caritas –Kabale Diocese) in enhancement of the social welfare among the rural poor people in Nyamweru Sub-county. This study was guided by the following objectives; to examine the role played by FBOs in enhancement of social welfare among the rural poor households; to identify the challenges faced by FBOs in enhancement of social welfare among the rural poor households and to establish the strategies that have been put in place to improve FBOs performance in enhancement of social welfare among the rural poor households. The study used a case study design which was backed up by qualitative approach. The study used a sample size of 80 respondents and these were selected both randomly and purposively. The data collection instruments used in this study included questionnaires, interview guide and focus group discussions. The analysis of data was done using descriptive statistics such as frequencies and percentages. From the findings, it was revealed that the roles of FBOs including Caritas Kabale Diocese are important in improving the welfare of rural poor households. As regards to Caritas Kabale Diocese, these roles include promotion of health in terms of HIV/AIDS awareness, promotion of agriculture, education, among others. Inputs, livestock and money are given to beneficiaries in order for them to start income-generating activities like Irish potato growing, goat and cow rearing, and poultry keeping. Based on the above findings, shortage of land, inadequate finance, and poor project selection, infertile soils due to poor conservation, poor infrastructure and poor accountability are some of the major challenges faced by Caritas Kabale Diocese. From the findings, it was recommended that Caritas Kabale Diocese needs to intensify their socio-economic empowerment programs so that rural poor households can be equipped with knowledge to reduce poverty and improve their welfare. There is need for the organizations to allow full and meaningful beneficiary participation. Involving beneficiaries in active participation allow them to make right choices of intervention and becomes responsive to such interventions.